2016
DOI: 10.4103/0301-4738.179725
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the early keratoconus based on corneal biomechanical properties in the refractive surgery candidates

Abstract: Context:Subclinical keratoconus is contraindication to refractive surgery. The currently used methods of preoperative screening do not always allow differentiating between healthy eyes and those with subclinical keratoconus.Aim:To evaluate biomechanical parameters of the cornea, waveform score (WS), and intraocular pressure (IOP) as potentially useful adjuncts to the diagnostic algorithm for precise detection of the early keratoconus stages and selection of refractive surgery candidates.Settings and Design:Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…There is no statistical difference regarding corneal compensated intraocular pressure (IOPcc) (14.17 ± 3.44 and 14.23 ± 2.01 mm Hg respectively with p value = 0.942). and this is in agreement with results of Pniakowska and Jurowski (21) , who found that Goldmann correlated intraocular pressure (IOPg) values were found lower in keratoconus group than normal and found also that there is no statistical difference in mean IOPcc observed between Group 2 and control group (P > 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is no statistical difference regarding corneal compensated intraocular pressure (IOPcc) (14.17 ± 3.44 and 14.23 ± 2.01 mm Hg respectively with p value = 0.942). and this is in agreement with results of Pniakowska and Jurowski (21) , who found that Goldmann correlated intraocular pressure (IOPg) values were found lower in keratoconus group than normal and found also that there is no statistical difference in mean IOPcc observed between Group 2 and control group (P > 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Also (21) stated that mean values of CRF (P < 0.0001 and P < 0.0001 respectively) were significantly lower in keratoconic eyes than in the control group…”
Section: Discussionmentioning
confidence: 91%
“…27 Ayrıca, Pniakowska ve ark.nın refraktif cerrahi adaylarında kornea biyomekanik özelliklerine göre erken keratokonusu saptamak için planladıkları çalışmalarında, KH ve KRF'nin refraktif cerrahi için başvuran hastalarda subklinik keratokonusu saptamak için klinik olarak yardımcı parametreler olabileceklerini belirtmişlerdir. 28…”
Section: Bulgularunclassified
“…Corneal biomechanical metrics are statistically significant between keratoconic and healthy corneas using both ORA 71,[75][76][77] (keratoconus showed lower CH and CRF value) and Corvis 71,[78][79][80] (keratoconus showed higher deformation amplitude), which could be useful to detect subclinical keratoconus. 81 Unfortunately, data provide for these devices have not proven to be a definitive keratoconus diagnostic value (able to differentiate between keratoconus, forme fruste and normal eyes) 71 because a substantial overlap exists with normal corneas, 82,83 and further research is necessary to obtain valid cut-off values to use in combination with more clinical data. 20,72,75,77,80,84,85 In summary, further clinical validation is necessary to inderstand the meaning of these biomechanical parameters obtainied with ORA and Corvis before they can be used in clinical practice.…”
Section: Biomechanical Devicesmentioning
confidence: 99%